Investigating multiple sclerosis genetic susceptibility on the founder population of east-central Sardinia via association and linkage analysis of immune-related loci. (December 2018) - Fazia, Teresa; Pastorino, Roberta; Foco, Luisa; Han, Lide; Abney, Mark; Beecham, Ashley; Hadjixenofontos, Athena; Guo, Hui; Gentilini, Davide; Papachristou, Charalampos; Bitti, Pier Paolo; Ticca, Anna; et al.
Background: A wealth of single-nucleotide polymorphisms (SNPs) responsible for multiple sclerosis (MS) susceptibility have been identified; however, they explain only a fraction of MS heritability. Objectives: We contributed to discovery of new MS susceptibility SNPs by studying a founder population with high MS prevalence. Methods: We analyzed ImmunoChip data from 15 multiplex families and 94 unrelated controls from the Nuoro Province, Sardinia, Italy. We tested each SNP for both association and linkage with MS, the linkage being explored in terms of identity-by-descent (IBD) sharing excess and using gene dropping to compute a corresponding empirical p -value. By targeting regions that are both associated and in linkage with MS, we increase chances of identifying interesting genomic regions. Results: We identified 486 MS-associated ( p < 1 × 10 –4 ) and 18, 426 MS-linked ( p < 0.05) SNPs. A total of 111 loci were both linked and associated with MS, 18 of them pointing to 14 non-major histocompatibility complex (MHC) genes, and 93 of them located in the MHC region. Conclusion: We discovered new suggestive signals and confirmed some previously identified ones. We believe this to represent a significant step toward an understanding of the genetic basis of MS.